Aerobic granular sludge shows enhanced resistances to the long-term toxicity of Cu(II). (August 2020) - Jiang, Yu; Liu, Yang; Zhang, Huining; Yang, Kai; Li, Jiangyun; Shao, Senlin
Abstract: Cu(II) is one of the most widely-existed heavy metal ions in industrial effluents. A high concentration of Cu(II) leads to strong toxic effects on microorganisms and sludge for treating industrial wastewater which often contains aromatic pollutants. Granular sludge has different characteristics compared with floc sludge, and it may exhibit unique responses to the high concentration of Cu(II). Therefore, in this study, the variations of sludge properties and pollutant removal were investigated in the aerobic granular sludge (AGS) system with 0, 5, and 10 mg L −1 of Cu(II). The results suggested that both levels of Cu(II) promoted protein secretion and bounded with extracellular polymeric substances; thus, led to more compact granules with better settleability. Cu(II) had limited impacts on the overall organic degradation and denitrification efficiency, while it exerted significant negative effect on nitrification. The average NH4 + -N concentration reached 1.4 ± 0.5, 6.7 ± 3.1, and 8.4 ± 1.5 mg L −1 in the effluent when the influent contained 0, 5, and 10 mg L −1 of Cu(II), respectively. The microbial community succession showed that no reduction was observed for the total relative abundance of main groups involved in organic removal such as Pseudoxanthomonas, Acidovorax, Acinetobacter, and Thauera . However, the growth of some functional groups such as Saccharibacteria for nitrification was inhibited by the toxic effect of Cu(II). These findings suggested that AGS could resist to the long-term toxic effects of Cu(II) by multiple rationales. Graphical abstract: Image 1 Highlights: 5 and 10 mg L −1 of Cu(II) promoted the settleability and stability of granules. Protein secretion increased while carbohydrate production decreased with Cu(II). Cu(II) had limited impacts on overall organic removal while retarded nitrification. The Cu(II)-tolerance strains for removal of organics and nitrogen were enriched.